Ibuprofen controlled release from E-beam treated polycaprolactone electrospun scaffolds - Rakina A. A. Apollinariya Aleksandrovna; Spiridonova T. I. Tatjyana Igorevna; Kudryavtseva V. L. Valeriya Lvovna; Kolesnik I. M. Iljya Maksimovich; Sazonov R. V. Roman Vladimirovich; Remnev G. E. Gennady Efimovich; Tverdokhlebov S. I. Sergei Ivanovich (2018, 2018)
Title screen